1978
DOI: 10.3758/bf03329612
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive self-mediation training with hyperkinetic children

Abstract: A group of hyperkinetic children from an area residential and educational facility was trained to verbally mediate behavior on problem-solving tasks by undergraduate volunteers. Such training involved the initial modeling of appropriate task behavior by the trainer and, by selective cuing and reinforcement, the child 's eventual imitation of the trainer-modeled behavior on the same tasks. Relative to time and treatment controls, the hyperkinetic children demonstrated significant changes on a number of measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Not unexpectedly, given the brevity of training, this treatment effect was not maintained at two-week follow-up testing. Moore and Cole (1978) randomly assigned fourteen 8-to 12-year-old hyperactive children from an educational residential treatment facility to one of three groups: cognitive training, attention control, or untreated control. Subject selection criteria included a diagnostic judgment of hyperkinesis by school personnel, an IQ of at least 85, and the absence of gross neurological impairment.…”
Section: Hyperactive Childrenmentioning
confidence: 99%
“…Not unexpectedly, given the brevity of training, this treatment effect was not maintained at two-week follow-up testing. Moore and Cole (1978) randomly assigned fourteen 8-to 12-year-old hyperactive children from an educational residential treatment facility to one of three groups: cognitive training, attention control, or untreated control. Subject selection criteria included a diagnostic judgment of hyperkinesis by school personnel, an IQ of at least 85, and the absence of gross neurological impairment.…”
Section: Hyperactive Childrenmentioning
confidence: 99%
“…Furthermore, cognitive styles are considered stable and enduring and are said not to appear to be easily modified by special training and instruction (Mann & Sabatino, 1985). Some studies (cf., Douglas, Parry, Marton, & Garson, 1976;Kirby, 1984;Moore & Cole, 1978) have, however, reported success in changing cognitive styles, such as impulsivity, even though not all cognitive styles appear to be equally amenable to alteration. One implication of this statement for the educational consultant is that it may be easier to adapt the teaching method to suit the learner's cognitive style rather than try to modify the learner's cognitive style to fit the teaching method.…”
mentioning
confidence: 90%
“…Recently cognitive programmes have been successful in modifying children with various problems, including children with 'cognitive impulsivity 1 (Finch et al , 1975), 'behaviour problems ' (Camp et al, 1977), 'hyperactivity' (Cole, 1978) and 'stealing behaviour' (Guidry, 1975;Stumphauzer, 197& He suggested that when the individual was confronted with a temptation to steal problem he was able to reflect and retrieve schemata, which he could then use to form the basis of strategies to solve the problem.…”
Section: Summary Of Findingsmentioning
confidence: 99%